Why do some physicians choose to tackle inequities in healthcare? - Victoria Nkunu; Kevin J. McLaughlin (BMC, 2018)
Abstract Background Despite the reputation of Canada's healthcare system as being accessible to all Canadians, certain populations continue to face inequities within our healthcare system. In addition to promoting fairness, addressing healthcare inequities has the potential to reduce healthcare costs, which is increasingly important as healthcare costs continue to rise. Intentionally or otherwise, physicians are often leaders in healthcare teams, but there is a paucity of literature on physicians' perceptions of the problem of healthcare inequities and their potential role in addressing inequities. In this pilot study, we use a grounded theory approach to explore contextual factors and mechanisms that associate with an individual physician's involvement (or otherwise) in initiatives to reduce healthcare inequity. Methods Using purposeful sampling and a set of a priori questions, we interviewed ten physicians - five of whom self-identified as being actively involved and five not actively involved in addressing healthcare inequities - to explore potential reasons for physicians choosing to address the causes of healthcare inequities. Results We identified contextual barriers (e.g., lack of knowledge and time) and facilitators (prior experience, protected time, mentorship and system supports) that we interpreted as interacting with the underlying mechanism (motivation to address inequities) to influence a physician's decision on whether or not to address healthcare inequities. Conclusion Based upon our findings we propose further studies to understand and/or overcome barriers to physicians being involved in addressing healthcare inequities.